PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SD PADA MATERI PERUBAHAN WUJUD BENDA - Mellinda, Dewi; Jayadinata, Asep Kurnia; Gusrayani, Diah (Jurnal Pena Ilmiah, 2017)
The Application of Contextual Teaching and Learning (CTL) model to increase student learning outcomeson material change object IV grade student of state elementary school of Ketib North Sumedang district Sumedang city. Research subject is IV grade student amounting to 24 student. The purpose of this research is to describe the prosess of applying the Contextual Teaching and Learning model outcomes on material change object IV grade student of state elementary school, and describe problems and solution. The research was conducted in three cycles. The source ata came from theacher, students, and documents. Data collection is observation and test. The validity of data using technique of data triangulation, member check and expert opinion. Learning result poin out that the purpose Contextual Teahing and Learning model can improving process and learning result science at IV grade.